IMPLEMENTASI MADU PADA PERAWATAN LUKA PASIEN APENDIKSITIS POST LAPARATOMI DENGAN MASALAH GANGGUAN INTEGRITAS KULIT/JARINGAN - Edi Wibowo; Erik Kuncoro; Made Suandika (Bajang Institute, 2022)
the response that arises after laparotomy causes nursing problems to damage tissue integrity. Implementing proper wound care procedures will speed up wound healing. Honey can be used in various modern medicine because it has a therapeutic effect. Methods: This study used a descriptive design in the form of a case study approach to nursing practice. The case study in this study examined the integrity of the skin and tissue of post-laparotomy patients after effective wound care using honey for 3 x 2 4 hours. Results: The results showed that the patient's skin/tissue integrity disorders before being given implementation were signs of redness and minimal bleeding in the wound, while impaired skin/tissue integrity after being given implementation for 3x24 hours showed that the wound looked cleaner, there was no redness, there was no minimal bleeding. and no pus. Conclusion: Nursing actions by doing wound care using honey can improve skin and tissue integrity which needs to be done in patients with impaired skin/tissue integrity disorders.